Development of ALD ZnO:Al as transparent conductive films. (April 2020) - Napoleonov, B; Marinova, V; Petrova, D; Blagoev, B; Avramova, I; Dimitrov, D
Abstract: We report the deposition of ultrathin Al-doped ZnO (AZO) films by using atomic layer deposition (ALD) and results from X-ray photoelectron spectroscopy (XPS) and photoelectrical measurements. The AZO films were deposited on glass, silicon and polyethylene terephthalate (PET) substrates and their structural and photoelectrical properties were measured and discussed. Based on the results, selected AZO films deposited on PAT were implemented as transparent electrodes in a polymer dispersed liquid crystal display device (PDLC). The electro-optical modulation characteristics of these devices are comparable to those of devices using commercial ITO electrodes.